Hydraulic analysis of a compound weir (triangular-rectangular) simulated with computational fluid dynamics (CFD) - Mattos-Villarroel, Erick Dante; Flores-Velazquez, Jorge; Ojeda-Bustamante, Waldo; Íñiguez-Covarrubias, Mauro; Díaz-Delgado, Carlos; Salinas-Tapia, Humberto (Tecnología y ciencias del agua, 2021)
To make an efficient delivery of water to irrigation users, it is necessary to have accurate dispositive to measure flow rates. These dispositive include triangular and rectangular weirs for measured flow rates ranges between 30 and 200 l s-1. However, the variation of flows in the execution of an agricultural year can be a factor of error in the volumetric delivery and a possible alternative solution is the use of a compound weir. The aim of this study was to analyze the hydraulic behavior of a triangular-rectangular weir, as a function of geometric and flow parameters and get a new global expression of the discharge coefficient. ANSYS Fluent was used to simulate the flow rates fluid, to discretized the dynamics of flow under specific conditions. The evaluation of the model with ANSYS Fluent, and its analysis, was carried out based on experimental data and the corresponding analytical solution. The Computational Fluid Dynamics (CFD) simulations showed statistical agreement with the laboratory data, finding a maximum error of 0.74 %. An expression of the global discharge coefficient was obtained and it was possible to analytically estimate the expenditure with a maximum error of 7.8 % with respect to experimental data. Thanks to the CFD simulation, it was possible to characterize the nappe and to analyze the effects of pressure and velocity on the discharge coefficient. The results allow us to conclude that a triangular-rectangular weir widely satisfies the precision required in the delivery of water to irrigation users.